2012
DOI: 10.1097/mpg.0b013e31823c3bfd
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Levels of Docosahexaenoic Acid Supply on Fatty Acid Status and Linoleic and α‐Linolenic Acid Conversion in Preterm Infants

Abstract: DHA supply dose dependently increased plasma DHA. Formula DHA levels of 0.33% matched plasma DHA status of infants fed HM. LC-PUFA synthesis was lower in infants fed HM than formulas with different DHA and low AA contents. With the LC-PUFA supplementation used, DHA in formulas did not inhibit AA or DHA synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…However, PUFA plasma concentrations were positively correlated with the dietary intakes for ARA, EPA, DPA, and DHA species. These data indicated that, as previously published, plasma total concentrations of the most physiologically abundant PUFAs reflect, in general, their recent dietary intakes[20,21]. In the absence of a study investigating the flux of different PUFA species, it is difficult to interpret why the intake-plasma correlations were significant in girls only for ARA (the most abundant n-6 species), whereas in boys it was significant for DPA, EPA, and DHA (all n-3 species).…”
supporting
confidence: 64%
“…However, PUFA plasma concentrations were positively correlated with the dietary intakes for ARA, EPA, DPA, and DHA species. These data indicated that, as previously published, plasma total concentrations of the most physiologically abundant PUFAs reflect, in general, their recent dietary intakes[20,21]. In the absence of a study investigating the flux of different PUFA species, it is difficult to interpret why the intake-plasma correlations were significant in girls only for ARA (the most abundant n-6 species), whereas in boys it was significant for DPA, EPA, and DHA (all n-3 species).…”
supporting
confidence: 64%
“…Selected long chain polyunsaturated fatty acids, particularly docosahexaenoic acid (DHA), seem to be essential for developing membranes, especially those of neurons and glial cells [68]. Long-term deficiency of DHA is associated with impaired neuronal development and function, and some studies have shown improved neuronal function as a result of supplements of DHA.…”
Section: Aggressive Parenteral Nutrition Of Preterm Infantsmentioning
confidence: 99%
“…The increased metabolic need of DHA during pregnancy can be compensated for by: (1) dietary intake; (2) increasing the capacity to metabolize ALA to DHA [ 19 ]; (3) preferential use of DHA reserves mobilized from adipose tissue [ 20 ]; and (4) saving DHA, because of amenorrhea during pregnancy [ 18 , 21 ]. Regarding diet, sources of n -3 PUFA are limited, and estimated intakes of EPA and DHA in various populations are below the recommended levels [ 22 ]; it is also known that DHA intake of women from industrialized countries is usually low.…”
Section: Introductionmentioning
confidence: 99%